Stroke patients after neurological inpatient rehabilitation: a prospective study to determine whether functional status or health-related quality of life predict living at home 2.5 years after discharge - Grässel, Elmar; Schmidt, Ralf; Schupp, Wilfried (International Journal of Rehabilitation Research, 2014)
We carried out a prospective study to determine whether stroke patients' functional status or health-related quality of life would predict whether they lived at home 2.5 years after discharge from neurological inpatient rehabilitation. We carried out a single-center prospective cohort study. The outcome 'home care' versus 'death' or 'institutionalization' (nursing home admission) was evaluated 30 months after discharge. A total of 204 stroke survivors with remaining moderate to severe functional deficits at admission to neurological inpatient rehabilitation were included. Clinical data were obtained at admission to and/or discharge from inpatient rehabilitation. Functional status was determined using the Barthel Index; health-related quality of life was assessed using the SF-36 and EQ-5D. The outcome was assessed by telephone interview. Predictors of living at home were calculated using binary logistic regression analysis. In total, 30 months after discharge, 75% of the stroke survivors were still living at home. Multivariate analysis showed that patients continued to live at home significantly more frequently when they had fewer mortality-relevant comorbidities (P=0.001), a higher BMI (P=0.040), a higher increase in functional independence during inpatient rehabilitation (P=0.017), and above all, a better health-related quality of life, measured using the EQ-5D (P<0.001), at discharge. Stroke survivors' health-related quality of life measured with the EQ-5D and the change in functional status during multimodal neurological rehabilitation appear to be the strongest clinically relevant long-term predictors of staying at home.
EVALuna2:23665